INTERAKSI GENOTIPE X MUSIM KARAKTER FISIOLOGI LATEKS DAN DAYA HASIL BEBERAPA GENOTIPE KARET HASIL PERSILANGAN TAHUN 1992 - Sayurandi Sayurandi; Desta Wirnas; Sekar Woelan (Warta Perkaretan, 2017)
Latex physiology characters and yield potential of rubber tree  (Hevea brasiliensis) are determined by genetic factor, environments, and genotype x environment interaction. The environmental conditions greatly influence latex physiology characters and latex yield potential are the monthly rainfalls. The objective of the research was to get information about the performance of latex physiology characters and yield potential of some promising rubber genotypes of crossing results in 1992 in dry and wet months period. The experimental design used was randomize completely design (RCD) with two factors and three replications. The first factor was genotypes consisted of 15 genotypes and 2 control clones of PB 260 and RRIC 100. The second factor was season consisted of the wet months period (August - November 2015) and dry months period (January - March 2016) based on classification of Oldeman. The research result showed that the genotype x season interaction effect was significant to sucrose content, inorganic phosphate content, thiol content, latex flow rate, plugging index, yield index, and latex yield potential. Genotype HP 92/542 was a more tolerant to seasonal changes and this genotype had high latex yield and more stable. The genotype can be developed as a new genetic material of superior rubber clone. Genotype HP 92/726 was also tolerant to seasonal changes but the genotype had low latex yield. The genotype HP 92/838 was intolerant to seasonal changes and the genotype had low latex yield and unstable.